Effects of housing conditions on behaviors and biochemical parameters in juvenile cynomolgus monkeys (Macaca fascicularis) - Koyama, Hironari (Exp Anim, 2018)
To investigate the effects of environmental enrichment on laboratory monkeys, we studied behavioral and physiological differences following changes in housing conditions. Ten male and female juvenile cynomolgus monkeys were first housed in pairs for 8 weeks after quarantine/acclimatization (singly housed) and subsequently housed alone for the next 8 weeks. Monkeys were subjected to evaluations of body weight gain, stereotypic or affiliative behaviors, cortisol, 4-ethylphenyl sulfate (4EPS) and catecholamine concentrations in biological samples, and blood chemistry tests under both housing conditions. Under paired housing, the stereotypic behavioral score decreased in both sexes, and the affiliative behavioral score increased in males and showed an increasing trend in females. Under single housing, the stereotypic score increased in both sexes, and the affiliative score decreased in males. Paired housing decreased serum calcium and urine cortisol concentrations in both sexes and decreased plasma cortisol in males and plasma 4EPS concentrations in females. The stereotypic score was positively correlated with serum calcium, plasma and urine cortisol, and plasma 4EPS concentration and negatively correlated with the affiliative score. The feces painting score, affiliative score, and plasma cortisol and serum calcium concentrations showed sex differences, suggesting differences in responsiveness to environmental changes between males and females. In conclusion, paired housing improved behavioral abnormalities in juvenile cynomolgus monkeys, suggesting that it may be an effective environmental enrichment paradigm. Calcium, cortisol, and 4EPS concentrations in biological samples may be useful indices for evaluating the effects of environmental enrichment.